Evaluasi Penerapan Keselamatan Dan Kesehatan Kerja Tambang Bawah Tanah Dalam Penggunaan Alat Pelindung Diri (APD) Guna Meningkatkan Mutu Keselamatan Kerja Pada Area Penambangan Batubara Lokasi CBP PT. CAHAYA BUMI PERDANA - Heri Prabowo; Alfa Candra Yarsila (Departemen Teknik Pertambangan FT UNP, 2019)
PT. Cahaya Bumi Perdana is a company engaged in underground coal mines. Underground mining has a great potential danger This potential hazard that causes underground mining is more frequent accidents, such as methane gas explosions. In addition, since the commencement of the operation of this underground coal mine in 2016 there have been several accidents which have been caused by human error (human errors) such as incomplete use of personal protective equipment (PPE). Therefore, it is necessary to evaluate occupational health and safety in use of PPE. This work health and safety evaluation aims to improve the quality or quality of work safety and reduce the number of accidents that occur. This evaluation includes: work safety system, company policy, equipment for Operational Procedure (SOP).Based on the observations of the authors in the field, there are still workers who ignore PPE (Personal Protective Equipment), such as not using a helmet (safety helmet), shoes (safety shoes), mask (respirator), glasses, gloves, ear plug, not wearing clothes while working, and lack of awareness of the consequences of the accident for yourself, the company, and the environment. The results of this evaluation activity will provide a solution to improve the quality of work safety in underground mines, which is to motivate workers to always comply with all established regulations, always be careful in working and always prioritize occupational safety and health. Efforts that can be done by the company to improve the quality / quality of occupational health and safety (K3) such as, conduct K3 training, conduct control and analysis of job performance, and place the position of employees or workers in the right position. This will improve work performance and improve the quality of health and safety of workers. With the results of this evaluation is expected to reduce the number of accidents that occur.Keywords : personal protective equipment, standard operational procedure, k3